Efektivitas Pergerakan Sederhana Ekstrimitas Terhadap Penurunan Kadar Glukosa Pasien Diabetes Mellitus Tipe 2 - Nurul Hidayah; Rifaatul Laila Mahmudah; Nurwidji; Yuna Annisa Salsabila (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2026)
Low physical activity contributes to poor glycemic control in patients with type 2 diabetes mellitus (T2DM). Low-effort, practical exercises that can be taught by nurses can improve short-term glycemia, but evidence for single-session simple limb movements is limited. Objective: To evaluate the acute effects of simple limb movements on capillary blood glucose in patients with T2DM. A quantitative, single-group pre-test-post-test study was conducted using a sequential sample of 15 patients with T2DM. Participants performed seven types of simple limb movements with varying repetitions (3–20 repetitions). Capillary blood glucose was measured immediately before and after each movement using a glucometer (Glucotest). Changes were analyzed using the Wilcoxon signed-rank test; significance was set at p ? 0.05. Results show several movement-repetition combinations produced statistically and clinically significant acute reductions in blood glucose. Specifically, open-hand grip at 10 repetitions showed a mean reduction (? ? ?9, p = 0.012), and wrist flexion-extension at 16 repetitions produced a greater reduction (? ? ?37, p = 0.043). Other movements, particularly specific ankle exercises, showed large numerical reductions in some trials but with greater inter-participant variability and inconsistent statistical significance. No major adverse events were reported. Brief, simple extremity movements can produce acute reductions in capillary glucose among some patients with T2DM, suggesting feasibility as a nurse-led intervention that can be implemented in the community. These findings require confirmation through larger randomized trials with continuous glucose monitoring to determine clinical utility and optimal protocols